Study of the reproductive potential of triploid oysters - Normand, Julien; Boudry, Pierre; Cornette, Florence; Ledu, Christophe (8th International Conference on Shellfish Restoration, 2005)
Reproduction was studied in triploid Crassostrea gigas, by crossing gametes from diploid and triploid parents.Triploids are able to produce viable gametes and their resulting progeny consisted in diploids, aneuploids and polyploids. Gametes from triploid parents frequently led to abnormal polar body formation, even before caryogamy occurred. A high frequency of aneuploids was observed, related to the missegregation of chromosomes during meiosis in triploids. This might be due to the observed incomplete synapsis in triploid eggs during Prophase I. The proportion of aneuploids decreased during larval development, reflecting differential mortality between ploidy levels. Due to limited gonadic development and high larval mortality rates, the reproductive potential (up to the pediveligere stage) of triploids was about 5.44% (female 2n x male 3n) and 1.47% (female 3n x male 2n) relative to crosses between diploids. Interestingly, polyploid larvae were mostly found in female 3n x male 2n progenies. Our results will be discussed from biological and environmental points of view.